2011
DOI: 10.1136/bmj.d1165
|View full text |Cite
|
Sign up to set email alerts
|

All cause and disease specific mortality in patients with knee or hip osteoarthritis: population based cohort study

Abstract: Objective To examine all cause and disease specific mortality in patients with osteoarthritis of the knee or hip.Design Population based cohort study.Setting General practices in the southwest of England.Participants 1163 patients aged 35 years or over with symptoms and radiological confirmation of osteoarthritis of the knee or hip.Main outcome measures Age and sex standardised mortality ratios and multivariable hazard ratios of death after a median of 14 years’ follow-up.Results Patients with osteoarthritis h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
511
1
18

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 613 publications
(572 citation statements)
references
References 41 publications
18
511
1
18
Order By: Relevance
“…Previous studies have demonstrated an increased risk of deep vein thrombosis and pulmonary embolism in patients with RA relative to the age and sex-matched general population without RA, likely due to the effects of systemic inflammation and endothelial dysfunction (50,51). Our findings may be the result of selection bias; it may be that healthier patients with RA are selected for THA and/or there may be an overall higher risk of venous thromboembolism among patients with advanced OA relative to the age and sex-matched general population without OA (52).…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies have demonstrated an increased risk of deep vein thrombosis and pulmonary embolism in patients with RA relative to the age and sex-matched general population without RA, likely due to the effects of systemic inflammation and endothelial dysfunction (50,51). Our findings may be the result of selection bias; it may be that healthier patients with RA are selected for THA and/or there may be an overall higher risk of venous thromboembolism among patients with advanced OA relative to the age and sex-matched general population without OA (52).…”
Section: Discussionmentioning
confidence: 69%
“…Quality-of-life studies suggest the impact of OA to be comparable to that of cardiac, neurological, and pulmonary diseases. [5][6][7] OA is also the leading cause of absence from work, costing the UK economy upwards of £18 billion annually and together with other musculoskeletal diseases accounts for almost one-tenth of the total annual NHS budget (£10 billion annually) and 12% of primary-care consultations [4,8]. Improving health-related quality-of-life for people with longterm conditions such as OA is a current NHS priority [9].…”
Section: Introductionmentioning
confidence: 99%
“…Limitations in physical function are associated with participation restrictions in people with knee osteoarthritis (OA) (1), and they predicted mortality independent of traditional risk factors (2). Compared with people without knee OA, those with knee OA have lower knee extensor strength (force-generating capacity) (3)(4)(5)(6) and impaired standing balance (5)(6)(7)(8), commonly defined as greater postural body sway or center of pressure (COP) displacement, suggesting that both reduced knee extensor strength and standing balance are potential impairments to be evaluated in the research and clinical settings as they may influence functional limitations in knee OA.…”
Section: Introductionmentioning
confidence: 99%